Mat Pilates improves lower and upper body strength and flexibility in breast cancer survivors undergoing hormone therapy: a randomized controlled trial (HAPiMat study) - Bertoli, Josefina [UNESP]; Bezerra, Ewertton de Souza; Winters-Stone, Kerri M.; Alberto Gobbo, Luis [UNESP]; Freitas, Ismael Forte [UNESP] (Taylor & Francis, 2022)
Purpose: To evaluate the effects of 24 weeks of Mat Pilates in breast cancer survivors (BCS) undergoing hormone therapy on lower and upper body muscle strength parameters and flexibility. Materials and methods: Forty-three BCS (≥40 years) with confirmed breast cancer stage 0–III undergoing hormone therapy were included. Participants were randomized into Mat Pilates (three times/week, 60 min session) or control group (relaxation activities every two weeks). The difficulty and number of exercise repetitions were increased over the weeks. Assessments were performed at three times points (baseline, 12 weeks, and 24 weeks). The generalized estimating equations (GEE) model was used to compare each outcome measure during the analysis of intention to treat (ITT) and “Per protocol analysis” (PPA). Results: The Pilates group presented significantly increased (p < 0.05) isometric flexor–extensor PT, and concentric and eccentric flexor PT and mechanical work (MW) after the intervention. Most of the upper body strength parameters, time to achieve maximal force (TFmax), maximal force (F max), and rapid force index (RFI) and right-left upper and lower body flexibility (p < 0.05) also improved. Conclusions: From our findings, we conclude that 24 and 12-weeks of Mat Pilates induced strength and flexibility gains for lower and upper body, respectively.Implications for rehabilitation Mat Pilates can be adapted to the fitness level of breast cancer survivors, with a great variety of exercises that can be performed using a mat only or a few pieces of equipment. Patients can practice at home to gain different health benefits (i.e., increasing strength, flexibility, and functional capacity level), which could positively impact on quality of life. Mat Pilates performed three times per week with systematized increments in exercise level, load, and volume throughout the intervention was effective to improve hip extensor–flexor muscles peak torque and mechanical work at different muscle contractions, as well as upper and lower body flexibility. Mat Pilates was also able to improve right-left shoulder abductor and trunk extensor muscles strength parameters after 12 weeks of intervention, as well as both surgery and non-surgery sides of the upper body.
Keywords: Breast neoplasms; endocrine therapy; exercise; muscle strength; range of motion